Body Mass Index and 25 Hydroxyvitamin D Status in Patients With and Without Heart Failure - DiCarlo, Christina (2011)
The purpose of this pilot study was to assess the association between 25-hydroxyvitamin D (25[OH]D) concentrations, vitamin D intake and sunlight exposure in patients with HF compared to healthy volunteers. Fourteen healthy volunteers 50 and older were recruited to compare with 14 patients with HF. Healthy volunteers were compared to HF patients by serum 25(OH)D concentrations, dietary vitamin D intake, weekly sunlight exposure, and other covariates. Independent samples t-tests and linear regression models were used to compare differences between HV and patients with HF. The mean serum 25(OH)D concentration was not significantly different between groups (Healthy volunteers 25.7±11.1 ng/ml, HF 20.4±10.2 ng/ml, p=.2) and no group effect was found in any multivariable models. BMI regardless of group was found to be inversely associated with serum 25(OH)D concentrations (p=.025). There was no difference in the dietary intake of vitamin D or calcium between groups. The healthy volunteers had significantly greater amount of sunlight exposure but this did not result in higher 25(OH)D when compared to those with HF. Our findings suggest that BMI has an important relationship with 25(OH)D concentrations regardless of a person being healthy or having HF.